2013
DOI: 10.3389/fphys.2013.00283
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-dependent K+ channels Kv1.3 and Kv1.5 in human cancer

Abstract: Voltage-dependent K+ channels (Kv) are involved in a number of physiological processes, including immunomodulation, cell volume regulation, apoptosis as well as differentiation. Some Kv channels participate in the proliferation and migration of normal and tumor cells, contributing to metastasis. Altered expression of Kv1.3 and Kv1.5 channels has been found in several types of tumors and cancer cells. In general, while the expression of Kv1.3 apparently exhibits no clear pattern, Kv1.5 is induced in many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 139 publications
(270 reference statements)
0
109
0
Order By: Relevance
“…First of all, several studies have demonstrated altered expression of Kv1.3 in some cancer specimens in comparison with normal tissue [6-8, 17, 18]. An increased expression of Kv1.3 channels was observed in the case of breast, colon, smooth muscle (leiomyosarcoma), skeletal muscle (alveolar rhabdomyosarcoma) and lymph node cancer [8,17] and in mature neoplastic B cells in chronic lymphocytic leukemia (B-CLL) [20]. A significantly increased expression of Kv1.3 channels that was positively correlated with tumor aggressiveness was recently observed in the case of leiomyosarcoma and alveolar rhabdomyosarcoma [8,18].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, several studies have demonstrated altered expression of Kv1.3 in some cancer specimens in comparison with normal tissue [6-8, 17, 18]. An increased expression of Kv1.3 channels was observed in the case of breast, colon, smooth muscle (leiomyosarcoma), skeletal muscle (alveolar rhabdomyosarcoma) and lymph node cancer [8,17] and in mature neoplastic B cells in chronic lymphocytic leukemia (B-CLL) [20]. A significantly increased expression of Kv1.3 channels that was positively correlated with tumor aggressiveness was recently observed in the case of leiomyosarcoma and alveolar rhabdomyosarcoma [8,18].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 99%
“…Recently, Kv1.3 channels are considered a new, potentially attractive molecular target in both cancer diagnostics and therapy [6][7][8][17][18][19][20]. First of all, several studies have demonstrated altered expression of Kv1.3 in some cancer specimens in comparison with normal tissue [6-8, 17, 18].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is postulated to be caused by the necessity of a transitory hyperpolarization, which supplies the driving force for Ca 2+ entry during G1/S progression [6]. Additional evidence supports that Kv1.3 would alter cell proliferation independently of ion conduction either by voltage-dependent conformational changes or by phosphorylation of the channel [4].…”
Section: Cancer Progressionmentioning
confidence: 99%
“…In this scenario, inhibition of Kv1.3 would be pointless [4]. On the other hand, Kv1.5 expression exhibits a significant correlation with the degree of malignancy in various kinds of tumors [6]. For all these reasons, future cancer therapies regarding Kv1.3 or Kv1.5 as targets would require exhaustive analysis and caseby-case consideration.…”
Section: Expert Opinionmentioning
confidence: 99%